Application of a collection model to estimate the revenue in the sub-basin of the Mamanguape river located on the coast of Paraíba state in Brazil territory - Vieira , Allan Sarmento; Fontgalland , Isabel Lausanne (Seven Editora, 2023)
The objective of this research is to estimate the collection of the Mamanguape sub-basin, located on the coast of Paraibano, with a mathematical model for charging for water use that considers volumes consumed, abstracted, transposed, and volumes of water used for effluent dilution. For this purpose, the main charging models adopted in Brazil were analyzed to finally define the best algorithmic basis, which considers the peculiarities of the sub-basin studied. With the chosen charging model research on water, pricing was carried out, to determine the optimal prices for consumption/capture and effluent discharge. Analyzing the results it was observed that the estimated collected resources do not provide a sustainable application of the real situation of the sub-basin analyzed, requiring more detailed studies to understand the peculiarities of the region, bearing in mind that the estimated collection is insufficient to provide the necessary infrastructure for the management system of the Mamanguape River/PB sub-basin. Therefore, the inaccuracy of the existing collection models to estimate the collection can compromise the investments and management, a situation that serves as a warning to the public water management agencies about the modeling to be used and the urgency of implementing the collection instrument, considering that it could improve the quality of the sub-basin studied. DOI:https://doi.org/10.56238/devopinterscie-196